Gross motor adaptation benefits from sleep after training. (23rd December 2019) - Bothe, Kathrin; Hirschauer, Franziska; Wiesinger, Hans‐Peter; Edfelder, Janina M.; Gruber, Georg; Hoedlmoser, Kerstin; Birklbauer, Juergen
Abstract: Sleep has been shown to facilitate the consolidation of newly acquired motor memories. However, the role of sleep in gross motor learning, especially in motor adaptation, is less clear. Thus, we investigated the effects of nocturnal sleep on the performance of a gross motor adaptation task, i.e. riding an inverse steering bicycle. Twenty‐six male participants ( M  = 24.19, SD  = 3.70 years) were randomly assigned to a PM‐AM‐PM ( n  = 13) or an AM‐PM‐AM ( n  = 13) group, i.e. they trained in the evening/morning and were re‐tested the next morning/evening and the following evening/morning (PM‐AM‐PM/AM‐PM‐AM group) so that every participant spent one sleep as well as one wake interval between the three test sessions. Inverse cycling performance was assessed by speed (riding time) and accuracy (standard deviation of steering angle) measures. Behavioural results showed that in the PM‐AM‐PM group a night of sleep right after training stabilized performance (accuracy and speed) and was further improved over the subsequent wake interval. In the AM‐PM‐AM group, a significant performance deterioration after the initial wake interval was followed by the restoration of subjects' performance levels from right after training when a full night of sleep was granted. Regarding sleep, right hemispheric fast N2 sleep spindle activity was related to better stabilization of inverse cycling skills, thus possibly reflecting the ongoing process of updating the participants' mental model from "how to ride a bicycle" to "how to ride an inverse steering bicycle". Our results demonstrate that sleep facilitates the consolidation of gross motor adaptation, thus adding further insights to the role of sleep for tasks with real‐life relevance.